2019
DOI: 10.5603/fhc.a2018.0025
|View full text |Cite
|
Sign up to set email alerts
|

NKT-like cells reveal higher than T lymphocytes expression of cellular protective proteins HSP70 and SOD2 and comparably increased expression of SIRT1 in the oldest seniors

Abstract: Introduction. NKT-like cells are "non-classical", "CD1d-independent" NKT cells which represent highly differentiated, conventional T lymphocytes coexpressing several NK (natural killer) associated receptors. They are effector lymphocytes of both innate and adaptive immunity and simultaneously regulatory cells of the adaptive immune system. They reveal large granular lymphocyte morphology and can mediate both MHC-restricted and MHC-unrestricted cytotoxicity, secrete many cytokines and modulate Th1 immune respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 49 publications
2
23
1
Order By: Relevance
“…HSP70 is not immunogenic but can participate in antigen processing after binding to polypeptides and enhance the immune response. A clinical trial injected purified HSP70 into children with brain cancer and found an antitumor effect and certain feasibility and safety in the antitumor therapy [54,55]. Another study has also shown that HSP70 inhibits brain tumor development in a C6 glioblastoma mouse model, which is associated with NK cell and T lymphocyte killing abilities of glioblastoma, as well as increased activities of NK cells and CD81 + T lymphocytes [55].…”
Section: Discussionmentioning
confidence: 99%
“…HSP70 is not immunogenic but can participate in antigen processing after binding to polypeptides and enhance the immune response. A clinical trial injected purified HSP70 into children with brain cancer and found an antitumor effect and certain feasibility and safety in the antitumor therapy [54,55]. Another study has also shown that HSP70 inhibits brain tumor development in a C6 glioblastoma mouse model, which is associated with NK cell and T lymphocyte killing abilities of glioblastoma, as well as increased activities of NK cells and CD81 + T lymphocytes [55].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that HSP70 is not immunogenic but can participate in antigen processing after binding to polypeptides and enhance the immune response. A clinical trial injected puri ed HSP70 into children with brain cancer and found an antitumor effect and certain feasibility and safety in the antitumor therapy [52,53]. Another study has also shown that HSP70 inhibits brain tumor development in a C6 glioblastoma mouse model, which is associated with NK cell and T lymphocyte killing abilities of glioblastoma, as well as increased activities of NK cells and CD81 + T lymphocytes [53].…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial injected puri ed HSP70 into children with brain cancer and found an antitumor effect and certain feasibility and safety in the antitumor therapy [52,53]. Another study has also shown that HSP70 inhibits brain tumor development in a C6 glioblastoma mouse model, which is associated with NK cell and T lymphocyte killing abilities of glioblastoma, as well as increased activities of NK cells and CD81 + T lymphocytes [53]. In the present study, we found that metformin increased HSF-1, MICA and HSP70 protein expression in SiHa and HeLa cells and also induced MICA expression on the surface of human cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…HSP70 is not immunogenic but can participate in antigen processing after binding to polypeptides and enhance the immune response. A clinical trial injected puri ed HSP70 into children with brain cancer and found an antitumor effect and certain feasibility and safety in the antitumor therapy [54,55]. Another study has also shown that HSP70 inhibits brain tumor development in a C6 glioblastoma mouse model, which is associated with NK cell and T lymphocyte killing abilities of glioblastoma, as well as increased activities of NK cells and CD81 + T lymphocytes [55].…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial injected puri ed HSP70 into children with brain cancer and found an antitumor effect and certain feasibility and safety in the antitumor therapy [54,55]. Another study has also shown that HSP70 inhibits brain tumor development in a C6 glioblastoma mouse model, which is associated with NK cell and T lymphocyte killing abilities of glioblastoma, as well as increased activities of NK cells and CD81 + T lymphocytes [55]. In the present study, we found that metformin increased HSF-1, MICA and HSP70 protein expression in SiHa and HeLa cells and also induced MICA expression on the surface of human cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%